Glasgow-Blatchford and Rockall score utility in predicting findings on video capsule endoscopy in patients admitted with overt small bowel bleeding - Ballester, Raquel; O'Connell, James; Costigan, Conor; Sengupta, Shreyashee; Manoharan, Thilagaraj; Martinez, Monserrat; Mc Namara, Deirdre (Endoscopy International Open, 2025)
Glasgow-Blachford (GBS) and Rockall scores are recognized tools to prioritize patients with upper gastrointestinal bleeding. Their utility in predicting findings on capsule endoscopy (CE) in patients with overt small bowel bleeding (OSBB) remains unclear. The aim was to assess use of these scores in predicting relevant findings on CE and outcome among patients with suspected OSBB.A retrospective analysis was performed from January 2019 to June 2022. Clinical parameters and scores were collected at presentation and at 24 hours. Univariate analysis used simple logistic regression, chi-squared test or Mann-Whitney as needed. ROC analysis was performed selecting the optimal cut-off point maximized by the Youden index.Seventy-nine patients were included, 62% of whom had relevant findings. The predictor showing the highest discrimination ability was the initial GBS (area under the curve [AUC] 0.625; 95% confidence interval [CI] 0.49–0.76). The optimal cut-off point was at least 4, with sensitivity 98%, specificity 30%, and accuracy 72%. Multivariable regression analysis showed inpatient status on CE (odds ratio [OR] 117.27; 95% CI 11.32–4492.93; P = 0.001), shorter time to CE (OR 1.02; CI 1.01–1.04; P = 0.018), higher initial GBS (OR 1.22; CI 1.06–1.43; P = 0.009), and higher GBS within 24 hours (OR 1.19; CI 1.04–1.37; P = 0.013) were predictive factors for relevant findings on CE, with a model AUC 0.802, sensitivity 91.8%, and specificity 63.3%.GBS and Rockall scores were useful in predicting relevant findings on CE in this cohort of patients with suspected OSBB. In patients with GBS 5 or higher, early CE during the same admission is warranted.
Keywords: Endoscopy Small Bowel; Small intestinal bleeding; Capsule endoscopy; Small bowel endoscopy; Endoscopy Upper GI Tract; Ulcers (peptic and other); Non-variceal bleeding